The Role of Emotional Intelligence In Cyberbullying: A Scoping Review - Azzahra Jasmine Puspoyudo; Jati Ariati (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Cyberbullying has increased alongside the rise of internet penetration during and after the COVID-19 pandemic, leading to negative consequences that necessitate protective factors. Emotional Intelligence (EI) is linked to the ability to manage emotions, especially in stressful situations such as cyberbullying. This study aims to analyze research on Emotional Intelligence (EI) in it’s role that influence and mitigate cyberbullying behaviors. This study employs a Scoping Review method, with data sourced from three databases (sciencedirect, scopus and springerlink), focusing on studies examining the relationship between EI and cyberbullying from 2019 to 2024. The findings indicate that Emotional Intelligence (EI) is key in understanding and preventing cyberbullying. These findings highlight the importance of promoting EI to foster a healthier online environment. However, this study does not comprehensively explore the effects of EI on cyberbullying due to limitations in population scope and time frame. Future research is expected to delve deeper into this topic and include a broader range of populations and study periods.